Some Puzzles of Politeness and Impoliteness within a Formal Semantics of Offensive Language - VOGEL, CARL (Springer, 2015)
Puzzles of linguistic politeness and impoliteness are outlined. A framework for articulating formal semantic theories of linguistic politeness and impoliteness is adopted. The framework provides a foundation for a semantic theory that builds on past argument that (im)politeness behaviors arise from offence management associated with disgust. The theory is shown to explain some of the puzzles of (im)politeness.
Conflict and Multimodal Communication: Social Research and Machine Intelligence
PUBLISHED
Computational Social Sciences series
Cham
Keywords: pragmatics; semantics; disgust; offence; impoliteness; politeness; Digital Humanities; Intelligent Content & Communications; Computational linguistics; DYNAMIC SEMANTICS; Formal Semantics; LINGUISTICS; Pragmatics; SEMANTICS; impoliteness; politeness